Rationale for the design of 3D-printable bioresorbable tissue-engineering chambers to promote the growth of adipose tissue - Faglin, Pierre (Sci Rep, 2020)
Tissue engineering chambers (TECs) bring great hope in regenerative medicine as they allow the growth of adipose tissue for soft tissue reconstruction. To date, a wide range of TEC prototypes are available with different conceptions and volumes. Here, we addressed the influence of TEC design on fat flap growth in vivo as well as the possibility of using bioresorbable polymers for optimum TEC conception. In rats, adipose tissue growth is quicker under perforated TEC printed in polylactic acid than non-perforated ones (growth difference 3 to 5 times greater within 90 days). Histological analysis reveals the presence of viable adipocytes under a moderate (less than 15% of the flap volume) fibrous capsule infiltrated with CD68(+) inflammatory cells. CD31-positive vascular cells are more abundant at the peripheral zone than in the central part of the fat flap. Cells in the TEC exhibit a specific metabolic profile of functional adipocytes identified by (1)H-NMR. Regardless of the percentage of TEC porosity, the presence of a flat base allowed the growth of a larger fat volume (p < 0.05) as evidenced by MRI images. In pigs, bioresorbable TEC in poly[1,4-dioxane-2,5-dione] (polyglycolic acid) PURASORB PGS allows fat flap growth up to 75 000 mm(3) at day 90, (corresponding to more than a 140% volume increase) while at the same time the TEC is largely resorbed. No systemic inflammatory response was observed. Histologically, the expansion of adipose tissue resulted mainly from an increase in the number of adipocytes rather than cell hypertrophy. Adipose tissue is surrounded by perfused blood vessels and encased in a thin fibrous connective tissue containing patches of CD163(+) inflammatory cells. Our large preclinical evaluation defined the appropriate design for 3D-printable bioresorbable TECs and thus opens perspectives for further clinical applications.